Ensemblance : the transnational genealogy of esprit de corps - Miranda, Luis de, 1971- (Edinburgh University Press, 2020)
Through several historical case studies from the last 300 years, Luis de Miranda shows how the phrase 'esprit de corps' acts as a combat concept with a clear societal impact. He also reveals how interconnected, yet distinct, French, English and American modern intellectual and political thought is.